Relative probability of recoilless Λ-production in nuclei in the plane-wave impulse approximation - Grypeos, M. E.; Lalazissis, G. A.; Massen, S. E.; Panos, C. P. (HNPS Advances in Nuclear Physics, 2020)
The problem of estimating the relative probability Ρ of recoilless Λ production in nuclei by means of the (K-,π-) reaction is investigated in the plane-wave impulse approximation, which leads to approximate expressions of the "Debye-Waller type". The values of the relevant average overlap integrals between Λ and neutron normalized harmonic oscillator wave func tions are close to 1.